Supercritical fluid extraction of alkaloids from Ilex paraguariensis St. Hil. - Cassel, Eduardo (2010)
In this work a study about extracts obtained from Ilex paraguariensis St. Hil. leaves with supercritical CO2 was carried out. Experiments were performed in a pilot-scale extractor with capacity of 1 L at pressure of 120, 150, 170 and 200 bar for four temperature conditions, 313.15, 323.15, 333.15 and 343.15 K. The experimental data were fitted using a mathematical model characterized by the existence of two distinct periods of extraction. Numerical results for the adjusted parameters correlated very well the supercritical extraction experimental data. The confidence of results obtained from mathematical model and experiments was assured through the chi-square test.